2022
DOI: 10.1177/03611981221097091
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation and Characterization of Extracted Recycled Asphalt Binder With Rejuvenators

Abstract: Rejuvenators are used in the asphalt industry to improve the performance and durability of aged binders and facilitate the use of recycled asphalt materials. The purpose of this study was to evaluate the impact of rejuvenator type and dose on the laboratory performance of asphalt binders. For this study, recycled asphalt pavement (RAP) and extracted RAP binder were obtained from an airfield reconstruction project located in Atlantic City, NJ. One petroleum-based (aromatic extract) and three organic-based (corn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…It was found that the use of waste maize oil resulted in a higher reduction in the viscosity of the bitumen, while fresh maize oil had lower stability at different temperatures. Samara, Offenbacker, Mehta, Ali, Elshaer, and Decarlo studied the effect of organic and petroleum products on the performance of bitumen modified by these oils. They reported that corn- and vegetable-oil-modified bitumen were less susceptible to aging compared to tall oil, and aromatic extract oil.…”
Section: Challenges Gaps and Perspectivesmentioning
confidence: 99%
“…It was found that the use of waste maize oil resulted in a higher reduction in the viscosity of the bitumen, while fresh maize oil had lower stability at different temperatures. Samara, Offenbacker, Mehta, Ali, Elshaer, and Decarlo studied the effect of organic and petroleum products on the performance of bitumen modified by these oils. They reported that corn- and vegetable-oil-modified bitumen were less susceptible to aging compared to tall oil, and aromatic extract oil.…”
Section: Challenges Gaps and Perspectivesmentioning
confidence: 99%
“…Such high stiffness of binders due to aging results in mixtures highly prone to cracking [6,7]. To reduce the influence of aged binders and improve the interaction between RAP material and virgin material, researchers suggest rejuvenation, which softens aged binders and improves their cracking resistance [8]. In addition, to address the variation in gradation and non-homogeneity in RAP materials, studies mention fractionation for controlled mixture designs [9].…”
Section: Introductionmentioning
confidence: 99%